TAFSIR AYAT PSIKOLOGI, Memaknai Ayat Al-Qur’an Tentang Resiliensi Jiwa Dan Urgensinya Dalam Kehidupan Sosial - Syafiq Mughni; Muhammad Marzuk (al-Afkar, Journal For Islamic Studies, 2022)
This study examines the ayat Qur'an which have an interpretation of Soul Resilience. Humans basically develop and grow according to their needs and desires. But not infrequently there are humans who are not able to adapt to develop in their new environment, with new demands and responsibilities. Therefore, there are many cases of suicide because they are unable to develop or individuals who are always slow in adapting. By using the Library Research method, this research will examine the verses of the Qur'an that contain the substance of soul resilience. From this study resulted in a finding, including the interpretation of the verses of the Qur'an containing the substance of Resilience contained in Surah al-A'rah ayat 50 regarding emotional regulation, Surah al-A'raf ayat 10 regarding impulse control, Surah az -Zumar ayat 53 on optimism, Surah an-Nisa' ayat 8 on empathy, Surah al-Imran ayat 160 on self-efficacy and Surah al-Hasyr ayat 18 on reaching out.